2018
DOI: 10.3892/ijo.2018.4666
|View full text |Cite
|
Sign up to set email alerts
|

Hsp70 (HSP70A1A) downregulation enhances the metastatic ability of cancer cells

Abstract: Heat shock protein 70 (Hsp70; also known as HSP70A1A) is one of the most induced proteins in cancer cells; however, its role in cancer has not yet been fully elucidated. In the present study, we proposed a hypothetical model in which the silencing of Hsp70 enhanced the metastatic properties of the HeLa, A549 and MCF7 cancer cell lines. We consider that the inability of cells to form cadherin-catenin complexes in the absence of Hsp70 stimulates their detachment from neighboring cells, which is the first step of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 73 publications
(76 reference statements)
4
39
0
1
Order By: Relevance
“…Examination of E-cadherin expression revealed that it disappeared to a greater extent when tumor cells with downregulated Hsp70 were co-cultivated with monocytes, data that show Hsp70 knockdown leads to a more rapid and effective EMT ( Figure 5B). Our data correlate well with a very recent report by Kasioumi et al [43], who demonstrated that Hsp70 regulates the steps of metastasis, including EMT and migration. The absence of Hsp70 in cancer cells appears to be the destruction of the Hsp70-dependent heterocomplexes of E-cadherin/catenins, which function like an anchor between neighboring cells [43].…”
Section: Discussionsupporting
confidence: 93%
“…Examination of E-cadherin expression revealed that it disappeared to a greater extent when tumor cells with downregulated Hsp70 were co-cultivated with monocytes, data that show Hsp70 knockdown leads to a more rapid and effective EMT ( Figure 5B). Our data correlate well with a very recent report by Kasioumi et al [43], who demonstrated that Hsp70 regulates the steps of metastasis, including EMT and migration. The absence of Hsp70 in cancer cells appears to be the destruction of the Hsp70-dependent heterocomplexes of E-cadherin/catenins, which function like an anchor between neighboring cells [43].…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, recent studies using small interfering RNA (siRNA) and short hairpin RNA (shRNA) have showed that HSP70 inactivation promotes cell transition to mesenchymal phenotype [185,190]. HSP70 downregulation destabilizes E-cadherin-catenin complexes allowing migration of tumor cells [185]. In addition, several reports have demonstrated that HSP70 inhibits TGF-β-induced EMT by decreasing Smad2 phosphorylation [191][192][193].…”
Section: Hsp70 In Metastasismentioning
confidence: 99%
“…Further research has found that inactivation of HSP70 showed to reduce tumor invasiveness and metastatic potential of breast, cervical and bladder cancer cell lines [183]. High HSP70 expression protects tumor cells against anoikis and amorphosis, forms of cell death that occur when cell loses its contact with extracellular matrix (ECM) [184,185]. In this regard, molecules involved in anoikis and amorphosis such as focal adhesion kinase (FAK) and Akt showed to be affected by HSP70 [186][187][188].…”
Section: Hsp70 In Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…This is also good evidence of HSP70's contribution to cancer cell stemness because resistance to apoptosis is known to be one of the characteristic signs of CSCs (see the subsection introduction). Overall, except one publication describing rather hypothetical mechanisms by which HSP70 might suppress CSC phenotype development [119], all other reports testified that intracellular HSP70 promotes cancer cell stemness.…”
Section: Intracellular Hsp70mentioning
confidence: 99%